2019
DOI: 10.1534/g3.119.400195
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Characterization of Maize Multiple Disease Resistance QTL

Abstract: Southern Leaf Blight, Northern Leaf Blight, and Gray Leaf Spot, caused by ascomycete fungi, are among the most important foliar diseases of maize worldwide. Previously, disease resistance quantitative trait loci (QTL) for all three diseases were identified in a connected set of chromosome segment substitution line (CSSL) populations designed for the identification of disease resistance QTL. Some QTL for different diseases co-localized, indicating the presence of multiple disease resistance (MDR) QTL. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Another haplotype identified on chromosomal bin 9.03 (Hap_9.2) identified in CAAM and DTMA panels was found to be located in close physical proximity to two closely spaced SNPs at 99.41 Mb identified in the Iodent material in a GWAS study conducted by Van Inghelandt et al 21 . QTLs for resistance to NCLB and for multiple disease resistance on chromosomal region 4.05 have been identified in various studies 11,59,62 , and our study also identified two haplotype blocks Hap_4.2 and Hap_4.3 in this chromosomal bin. Overall, it was found that several SNPs/haplotypes identified in this study are in close proximity to previously reported major genes and QTL clusters, but many novel genomic regions were also discovered that could be environment and germplasm-specific.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Another haplotype identified on chromosomal bin 9.03 (Hap_9.2) identified in CAAM and DTMA panels was found to be located in close physical proximity to two closely spaced SNPs at 99.41 Mb identified in the Iodent material in a GWAS study conducted by Van Inghelandt et al 21 . QTLs for resistance to NCLB and for multiple disease resistance on chromosomal region 4.05 have been identified in various studies 11,59,62 , and our study also identified two haplotype blocks Hap_4.2 and Hap_4.3 in this chromosomal bin. Overall, it was found that several SNPs/haplotypes identified in this study are in close proximity to previously reported major genes and QTL clusters, but many novel genomic regions were also discovered that could be environment and germplasm-specific.…”
Section: Discussionsupporting
confidence: 77%
“…Meta-QTL studies on resistance to multiple foliar diseases identified about 147 multiple disease resistance mQTLs for three foliar diseases, NCLB, Southern leaf blight (SLB) and Gray leaf spot (GLS) and identified bins 3.04-08, 5.04-07, and 8.05-06 that are significant for resistance to these diseases 10 . QTLs on chromosome 3 bin 3.04-08 has been identified in many studies for NCLB and SLB 11 . QTLs on chromosome bin 5.04 and 5.06-07 were detected in different mapping studies for NCLB and GLS resistance 11 .…”
mentioning
confidence: 99%
“…To test our hypotheses, we compared microbiome composition of near-isogenic plants with and without introgressed chromosome segments that conferred MDR (Lopez-Zuniga et al, 2019;Martins et al, 2019). Two MDR inbred lines (NC304 and Ki3) were crossed with H100, a disease-susceptible line.…”
Section: Field Experimental Designmentioning
confidence: 99%
“…4). However, the effects of these introgressions on the microbiome were much more variable among environments than their effects on disease resistance (Lopez-Zuniga et al, 2019;Martins et al, 2019). This suggests that changes in the relative abundance of potentially protective microbes is unlikely to be a major mechanism by which these particular MDR alleles confer improved disease resistance.…”
Section: In Adult Plants Introgressed Qtl Improved Disease Resistancmentioning
confidence: 99%
See 1 more Smart Citation